Pengaruh Motivasi Dan Pengetahuan Terhadap Minat Berinvestasi Saham Di Pasar Modal Syariah - Sabik Khumaini; Ayunda Jinan Nadiya (Prodi Perbankan Syariah FAI UMT, 2021)
This study aimed to determine the influenced of motivation and knowledge of students the study program Islamic banking on invest interest stock in the Islamic Capital Market. The sample in this research is 67 students. The test of the instrument was analyzed by using validity test and reliability test. The analysis technique used in this study is the descriptive statistics, classic assumption test and multiple linear regression. The classical assumption test consists of, normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Hypothesis test use the determination test, F test, and t test. The results showed that, motivation partially has an insignificant positive influence on invest interest stock in the Islamic Capital Market. Knowledge partially had a significant positive influence on invest interest stock in the Islamic Capital Market. Meanwhile, simultaneously based on the results of the F statistical test, the independent variables of motivation and knowledge together have a significant and positive influence on the dependent variable invest interest stock. The predictive ability of these two variables on invest interest stocks is 46.0%, while the remaining 54.0% is influenced by other variables outside the regression model.